Compressive and Shear Wave Velocity Profiles using Seismic Refraction Technique. (April 2016) - Aziman, M; Hazreek, Z A M; Azhar, A T S; Haimi, D S
Abstract: Seismic refraction measurement is one of the geophysics exploration techniques to determine soil profile. Meanwhile, the borehole technique is an established way to identify the changes of soil layer based on number of blows penetrating the soil. Both techniques are commonly adopted for subsurface investigation. The seismic refraction test is a non-destructive and relatively fast assessment compared to borehole technique. The soil velocities of compressive wave and shear wave derived from the seismic refraction measurements can be directly utilised to calculate soil parameters such as soil modulus and Poisson's ratio. This study investigates the seismic refraction techniques to obtain compressive and shear wave velocity profile. Using the vertical and horizontal geophones as well as vertical and horizontal strike directions of the transient seismic source, the propagation of compressive wave and shear wave can be examined, respectively. The study was conducted at Sejagung Sri Medan. The seismic velocity profile was obtained at a depth of 20 m. The velocity of the shear wave is about half of the velocity of the compression wave. The soil profiles of compressive and shear wave velocities were verified using the borehole data and showed good agreement with the borehole data.